Effect of Extract and Caffeic Acid Phenethyl Ester on Apoptosis of Odontoblast Cells - Ira Widjiastuti; Agus Subiwahjudi; M. Aditya Syahputra; Grace Angelina Samuel; Ni Putu Sawitri Mega; Cinitra Anindya (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Propolis is a resinous hive product collected by bees from tree buds and mixed with secretedbee wax to both avoid bacterial contamination in the hive and seal it. It is known to have a wide spectrumof pharmacological properties, including anti-inflammatory, antioxidant, antibacterial, antiviral, and antifungal abilities. Apoptosis tests were performed on odontoblast cells in rats (Rattus novegicus) to assessthe viability of propolis extract and caffeic acid phenetyl esters (CAPE) as alternative candidates for pulpcapping agents in conservative dentistry treatment. Objective: To examine the apoptosis activity of propolisextract and CAPE as capping materials on odontoblast cells. Methods: This study was designed as a posttest only control group laboratory experiment. The rats were randomly divided into three groups. Pulpexposures were performed on the occlusal surface of the right maxillary first molars. In the first group, thecontrol group, glass ionomer cement (GIC) was directly applied to the pulp exposure. In the second group,the sample group, propolis extract was applied to the pulp exposure, and in the third group, CAPE wasapplied to the pulp exposure. All cavities were then filled with GIC as a permanent filling. Animals weresacrificed on the first and fourteenth days. The direct counting method of histological examination was basedon the apoptotic odontoblasts, using the terminal deoxyribonucleotidyl transferase dUTP nick end labeling(TUNEL) assay technique. Result: There was a greater number of apoptotic odontoblasts in the controlgroup, followed by the CAPE group and, lastly, the propolis extract group. Conclusion: The apoptosisactivity of the propolis extract is lower than that of CAPE.